Avaliação de dois genótipos de Leucena cultivadas em consórcio com o capim Massai no bioma Cerrado - Luiz Eduardo Santos Lazzarini (2012)
The low productivity of forages in grazing systems and the widespread deficiency of proteins constitute a major limitation for cattle production in the tropics. A viable option to overcome the problem consists in offering herbaceous legumes, shrubs or trees that can be a source of food of good quality contributing to the increase of animal production. This experiment was conducted to evaluate the potential use of two cultivars of leucaena (Leucaena leucocephala cv. Cunningham and Hybrid Leucena 11x25) for ruminant feed. It was measured the dry matter production per hectare of fresh plant, crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), neutral detergent insoluble protein (NDIP), acid detergent insoluble protein ( PIDA), in vitro kinetics of rumen fermentation by the semiautomatic gas production technique and Mimosine concentration. It was applied a completely randomized factorial arrangement (2 varieties x 3 cutting ages x 5 replicates). The design was evaluated by the generalized linear model with multiple comparisons of means performed by the least squares mean. The cultivar Cunningham had greater DM / ha compared to cultivate 11x25. Comparing cutting ages, the highest yields of DM / ha were observed in plants harvested at 42 days. The CP did not differ statistically. The 11x25 cultivar had higher NDF and ADF compared toCunningham. Regarding to the DM fermentation characteristics Cunningham had the greatest potential and rate of gas production, higher ED using passage rates of 2 and 5% / h. The fermentation parameters of DM were similar when comparing cutting ages. For the levels of Mimosine, it was verified a reduction according to the cutting age, and highest levels for the cultivate 11x25. The results indicate the superiority of the cultivar Cunningham for productivity and nutritional value. Under the experimental conditions of this study is recommended to cut the Leucena cultivars at 42 days of growth.